TEACHERS’ ATTITUDE TOWARDS PEER OBSERVATION AT NAJRAN UNIVERSITY: A CASE STUDY - Soada Idris Khan (University of Kuningan, 2019)
The present research paper aims to analyze teachers’ attitude towards peer-observation and suggest remedies to improve practice of peer-observation. As part of the methodology, the researcher selected twenty questionnaires as a sample of this study. Twenty teachers involved in peer-observation (as observer and participants) were also interviewed and their suggestions and opinions were taken into consideration to improve practice of peer-observation at PYP, Najran University. The analysis of data showed that teachers do not whole-heartedly support peer-observation. The study also found that most of the teachers are not well familiar with the concept and application of peer-observation. They often consider evaluation as an excuse to termination. The study accomplishes that a teachers’ performance/ability cannot be judged in 20-30 minutes. Therefore, the study recommends that there must be many peer-observations for the same class and the best one must be assessed. The study also suggests organizing seminars and workshops to orient teachers to the process and advantages of peer-observation.